Pre-Hispanic settlements in hydrometeorologically susceptible areas during the late Holocene: The Upper Delta of the Paraná River Case - Castiñeira Latorre, Carola (2017)
In this paper, we present the results of the geoarchaeological studies carried out in two archaeological localities of the Upper Delta of the Paraná River (Argentina). The main objective of these studies is to depict the pre-Hispanic strategies involved in the colonization and settlement of southern South America wetlands. Paraná Delta is one of the most conspicuous areas of these lowlands and comprises a large wetland macrosystem. Its current geomorphological configuration was established after the last transgressive mid-Holocene event c. 6000 14C yr BP. In this environment, a high ecological heterogeneity, with diverse and abundant tropical and temperate biota, was developed. These features were important factors to the human colonization and utilization of these wetlands. However, this environment has the highest hydrometeorological susceptibility of La Plata basin. This susceptibility had an impact on settlement systems and resource exploitation strategies established in the area since at least 2000 14C yr BP. These strategies involved at least two settlement types: semi-permanent residential camps and transitory camps oriented to exploit particular resources. The semi-permanent settlements were located in anthropogenic elevated mounds, locally known as ‘cerritos’, and were not subjected to seasonal inundations. Conversely, the transitory camps are found in levees exposed to recurrent flooding.